EFFECT OF SURFACE OXYGEN GROUPS OF CARBON SUPPORTS ON THE CHARACTERISTICS OF PD/C CATALYSTS - SUH, DJ; PARK, TJ; IHM, SK (PERGAMON-ELSEVIER SCIENCE LTD, 1993)
The effect of surface oxygen groups on the properties of carbon-supported palladium catalysts for liquid-phase hydrogenation of dinitrotoluene has been investigated. Activated carbons and carbon black were subjected to oxidative treatments in order to introduce surface oxygen groups. The surface oxygen groups were characterized by acid-base titrations, TPD of the decomposition products (CO and CO2), and infrared spectroscopy. Palladium on carbon catalysts were prepared with these carbons by alkali hydrolysis and liquid-phase reduction, and the palladium dispersion was determined from pulsed oxygen titration measurements. The palladium dispersion increased with the increasing amount of surface oxygen groups. but the catalytic activity did not improve proportionally. probably due to more uniform distribution of palladium particles into the smaller pores. The catalytic activity may be explained by metal dispersion, metal location throughout the entire pore structure, and surface nature of the support. In addition, the surface oxygen groups were found to play an important role in hydrogen adsorption/titration on the palladium surface, thus facilitating the hydrogen spillover even at low temperatures.
Keywords: PLATINUM; HYDROGEN; HETEROGENEITY; DISPERSION; PALLADIUM; SIZE